(untitled) (Fiep Bulletin - online, 2014)
This article has an objective to consider the importance of physical activities that contribute for an educational process of emotional balance and social integration of pre-adolescents with violent behavior at the school, being considered that the school is a social environment of Inter-relations, in which this individual remains good part of the time. When they express movement day by day in the school, these students acquire new knowledge. The quality of these movements and the application of appropriate pedagogical resources make difference in the educational process. The type of the game used in the physical activities, contribute for the success or the failure of the objectives of the teacher. When the activities are directed to playful, we perceive that the pupils have more involvement, creativity and pleasure, therefore, the importance are in playing and interacting. The lessons of Physical Education for individuals between six and twelve years old are very important and contribute so much for the growth and the development of them. The specialist must have basic knowledge with boarding in the biological aspects of the physical activity, the learning of basic and specific activities of the motor development, intellectual and affective-social and the development period of each age band, thus taking care of to the necessities and lacks of the pupils, opting to activities that promote the union for the search of common objectives, where the success of one is also the success of all, excessively, favoring, in that way, the sympathy , the esteem, recognizing and expressing the frank dialogue as form of relation.